Задзеркалля в романі "Розпізнавання образів" Вільяма Гібсона - Бовсунівська, Т.В. (Слово і Час, 2019)
У статті йдеться про поетику роману, основаного на принципах літературного кіберпанку.
Вільям Гібсон, засновник кіберпанку як жанру, у романі “Розпізнавання образів” використав
образ задзеркалля з книги Льюїса Керролла “Аліса в задзеркаллі” як лейтмотив, ремінісцентно
згорнений та оприявлений тільки у свідомості головної героїні Кейс Поллард. Проаналізовано
семантику лейтмотиву задзеркалля та його функціональність у романі, а також відповідність
щодо принципів трансреалізму й постгуманізму. Ідеться про “поетику гормонів” замість “поетики
почуттів”. Стани головної героїні пояснюються не вчинками чи періодом доби, а гормональним
розладом; наукова обізнаність уплітається в метафоричність, і художній стиль В. Гібсона стає
незворотно кіберпанковим. The paper deals with the poetics of the novel, based on the principles of literary cyberpunk. William
Gibson, the founder of cyberpunk as a genre, in the novel “Pattern Recognition” used the lookingglass
image of Lewis Carroll’s book “Through The Looking-Glass And What Alice Found There” as a
leitmotif, reminiscently curved and shown only in the mind of the main character Case Pollard. The
paper analyzes the semantics of the leitmotif of looking-glass and its functionality in the novel, as well
as the conformity with the principles of transrealism and posthumanism. The state of the main character
is not explained by some acts or periods of the day, but by hormonal disorder; the scientific awareness
is intertwined with the metaphoric field. Thus William Gibson’s artistic style acquires obvious features
of cyberpunk. If Alice was just a weird kid who invented the world of fairy-tale creatures, Gibson’s
character Case lives in a transreal world, full of various man-made modifications of space and humans.
The modern Case-Alice does not invent anything, because the fairy-tale situation of her life is already
embedded in the nature of civilizational development. Case as a heroine of the novel fully complies
with the requirements of transrealism: she is not ‘normal’, she has a diagnosis and medical history.
Тhe ‘F: F: F’ program (fragments) is created by an autistic Russian girl. The neurotic characters that
Case meets are atypical, all in their own way. That is why the world around modern Alice, who is Case
at the same time, is distorted by the abnormality, which is not hidden by the heroes. The cyberspace
of modern human existence transforms all the sores of society into customary artificial symbols of
degradation – posthumanistic codes.